IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society 2013
DOI: 10.1109/iecon.2013.6699179
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of VSC-based HVDC system under DC faults

Abstract: This paper analyzes the behavior of a Voltage Source Converter Based HVDC system under DC cable fault conditions. The behavior of the HVDC system during a permanent line-to-earth fault is analyzed, outlining the systems configuration and behavior at each stage of the fault timeline. Operation of the proposed system under a single earthing configurations, i.e. Converter (solid) earthed/AC transformer unearthed, was analyzed and simulated, with particular attention paid to the converters operation. It was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…16, since focus is on M-HVDC control techniques rather than earthing configurations. All earthing used within a M-HVDC grid is solid, that is, low impedance [27]. This aspect will be addressed in future research, when assessing dc grid faults.…”
Section: M-hvdc Earthing Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…16, since focus is on M-HVDC control techniques rather than earthing configurations. All earthing used within a M-HVDC grid is solid, that is, low impedance [27]. This aspect will be addressed in future research, when assessing dc grid faults.…”
Section: M-hvdc Earthing Configurationmentioning
confidence: 99%
“…The system transfers power between three mainland ac grids through submarine cables and the wind farm is tapped with a tee connection. It is potentially the first application of a meshed M-HVDC network, and is off the U.K. coast [27]. Two control scenarios are considered.…”
Section: Generalized Droop Control Strategymentioning
confidence: 99%
“…In the subsequent simulation studies, a permanent single line-toearth fault occurs at t = 0.5 s on the positive DC line of the system between the sending and receiving end converters. As previously stated, implementation of the future MTDC system will likely be based on MMC technologies, which have many advantages over two-level converters including the elimination of the common DC-link capacitance which results in a significant reduction in the DC fault current produced [10]. Although there are a number of proposed topologies for multi-level converters, to keep the system in line with existing MMC systems a half-bridge topology will be used in this example [24].…”
Section: System Earthing Configurationsmentioning
confidence: 99%
“…The previous literature also has reported the transient over‐current and over‐voltage (TOV) phenomena for the conventional voltage source converter‐based HVDC system under DC faults. In [17, 18], Rafferty et al concluded that the formation of Earth loops within the system would lead a substantial over‐current through the converter and result in system configuration oscillation under a DC pole‐to‐ground fault. In [19], OV of the DC bus when gating signals of the converter were stopped for HBSMs based MMC was analysed, and a corresponding sequence with blocking the gating signals at the zero‐crossing point of each arm current was proposed.…”
Section: Introductionmentioning
confidence: 99%